China’s Hui Muslims’ wisdom of coexistence - Mai, Jianjun (Penerbit Universiti Sultan Zainal Abidin, 2024)
The Hui is the largest Muslim minority group in China, descended from ancient Arab and Persian merchants in the 7th century and mid-Asian war captives of the Mongol army in the 13th century. Immersed in an environment where more than 90% of the total population is non-Muslim Chinese, and whose dominant ideology is Confucianism, the Hui Muslims have undergone significant pressures to integrate into the mainstream society to avoid being marginalized on the one hand and retain their Islamic faith on the other hand. Responding to the challenges, the Hui Muslims employed two major strategies i.e. external accommodation policy and dawah with wisdom to survive and coexist with the dominant Confucian ideology in China. This study explores the coexistence strategies employed by the Hui Muslims during Ming and Qing dynasties. It provides important insights for Muslim minority groups to cope with dominant ideologies of the societies where they live.